Short-and long-term effects of ischemic postconditioning in STEMI patients: a meta-analysis. Issue 1 (December 2015) - Gao, Jing; Luo, Junyi; Liu, Fen; Zheng, Yingying; Chen, Bangdang; Chen, Qingjie; Yang, Yining
Abstract Background Compelling evidence from large randomized trials demonstrates the salutary effects of ischemic postconditioning on cardioprotection against ischemic/reperfusion injury. However, some studies appear negative findings. This study was designed to assess the short-and long-term effects of postconditioning (Poc) in studies including evolving ST-elevation myocardial infarction (STEMI). Methods Relevant studies were identified through an electronic literature search from the PubMed, Library of Congress, Embase, Cochrane Central Register of Controlled Trials, and ISI Web of Science. Studies published up to December 2014 were eligible for inclusion. Patients older than 18 years presenting within 12 h of the first STEMI and eligible for angioplasty were considered for the study. Results The 25 trials allocated 1136 patients to perform locational postconditioning cycles at the onset of reperfusion and 1153 patients to usual percutaneous coronary intervention (PCI). Ischemic postconditioning demonstrated a decrease in serum cardiac enzymes creatine kinase (CK) and CK-MB (P  < 0.00001 andP =0.25, respectively) in the subgroup analysis based on direct stenting. Reduction in infarct size by imaging was showed during7 days after myocardial infarction (P =0.01), but not in the longterm (P  = 0.08). The wall motion score index was improved in both the short term within 7 days (P  = 0.009) and the long term over 6 months after receiving Poc (P  = 0.02). All included studies were limited by the high risk of performance and publication bias. Conclusions Ischemic postconditioning by brief interruptions of coronary blood flow at the onset of reperfusion after PCI appears to be superior to PCI alone in reducing myocardial injury and improving left ventricular function, especially in patients who have received direct stenting in PCI.